Plan estratégico para la empresa Disur de la ciudad de Yantzaza, cantón Yantzaza – provincia de Zamora Chinchipe - Aleaga Trujillo, Evelyn Valeria (2017)
The title of this research work is: "PROPOSAL FOR A STRATEGIC PLAN FOR THE DISUR COMPANY OF THE CITY OF SHOP, OF THE CITY, PROVINCE OF ZAMORA CHINCHIPE", the general objective guiding the present research is framed in Elaborate a "Strategic Plan for the company DISUR of the city of Yantzaza". The methodology used during the development of the present study was based on the use of different methods as follows: inductive, deductive, analytical, synthetic, it was also necessary to use techniques such as observation, employee survey and Sample of the clients of the company and the interview made to the owner of the company. During the process of preparing the Strategic Plan for the company DISUR, the following procedure had to be followed: In the first instance, the analysis of factors external to the company was carried out. An analysis was made of the social, economic, political, technological, environmental and competitive factors of the environment, as well as Porter's forces. Analysis was able to obtain accurate information about the main opportunities and threats for the company. In the second place, the analysis of internal factors of the company was carried out, for which an interview was applied to the Manager; As well as a sample of 313 external clients and all 15 employees, as a result of the field study, it was possible to obtain first hand enough information that allowed identifying the main strengths and weaknesses of the company. Identification through internal and external analysis was obtained the main strengths, weaknesses, opportunities and threats of the company DISUR, served as the basis for the structure of the SWOT matrix, and later the matrix of HIGH IMPACT, of which Achieved the following strategic objectives: • Capture more customers and increase sales of the services of the DISUR company. • Improve the knowledge and skills of the DISUR company. • Increase the number of customers, by publicizing widely the services offered by the company. • Improve the performance of each employee of the company. At the end of the present paper we present a series of conclusions, among which we point out the following: It is concluded that the owner and the employees of the company DISUR, stated that there is no Strategic Plan, that allows him to improve the performance of the employees to fulfill the tasks, activities and functions in the company. The internal analysis made it possible to detect the strengths and weaknesses of the company to develop the EFI matrix, where the value of 2.41 points was obtained, which means that the strengths predominate over the weaknesses, therefore it is necessary to establish operational plans to counteract Weaknesses and take advantage of the company's internal strengths. In the external analysis we detected the opportunities and threats of the environment of the company, with the analysis was obtained the EFE matrix, which gave a value of 2.45 points, and as a result gives us that there is a predominance in the company of threats over opportunities. Subsequently, a proposal was made for a Strategic Plan for the DISUR company in the city of Yantzaza. And finally, the total budget was made in the amount of US $ 7,360.00, which will be financed by the company to fulfill the Strategic Plan. Among the recommendations we have: To implement a strategic plan in the study company, in order to improve the current situation of the DISUR company, to promote greater commitment on the part of the employees and therefore to obtain optimal results in the fulfillment of the commercial activity of the same in the city of Yantzaza. That the owner of the company DISUR, apply the proposal of the Strategic Plan, carried out in the investigation and in this way improves the current situation of the company. A constant training of all the personnel of the company in customer service, human relations, leadership, finances that is indicated in the proposed Training Plan must be carried out. Ensure the full and timely financing of the total budget, in order to implement the Strategic Plan, without financial resources difficulties.